Creación de una normativa que garantice el resarcimiento del daño moral a las niñas, niños y adolescentes, víctimas de abuso sexual - Macías Jaramillo, Lady Rosmary (2015)
This legal research project entitled "Creating a policy that guarantees compensation for moral harm to children and adolescents, victims of sexual abuse " takes an approach to the situation that occurs around the application of Art. 11 , no. 9 of the Code of Criminal Integral under the Constitutional Law. In which some aspects faced by people who are victims of sexual abuse and lack of protection of rights by the state are pointed